Reductions in child mortality levels and inequalities in Thailand: analysis of two censuses - Patama Vapattanawong (2018)
Background: Thailand's progress in reducing the under-five mortality rate (U5MR) puts the country on track to achieve the fourth Millennium Development Goal (MDG). Whether this success has been accompanied by a widening or narrowing of the child mortality gap between the poorest and richest populations is unknown. We aimed to measure changes in child-mortality inequalities by household-level socioeconomic strata of the Thai population between 1990 and 2000. Methods: We measured changes in the distribution of the U5MR by economic strata using data from the 1990 and 2000 censuses. Economic status was measured using household assets and characteristics. The U5MR was estimated using the Trussell version of the Brass indirect method. Findings: Average household economic status improved and inequalities declined between the two censuses. There were substantially larger reductions in U5MR in the poorer segments of the population. Excess child mortality risk between the poorest and richest quintile decreased by 55% (95% CI 39% to 68%). The concentration index, measured using percentiles of economic status, in 1990 was -0·20 (-0·23 to -0·18), whereas in 2000 it had dropped to -0·12 (-0·15 to -0·08), a 43% (22% to 63%) reduction. Interpretation: These findings draw attention to the feasibility of incorporating equity measurement into census data. Thailand has achieved both an impressive average decrease in U5MR and substantial reductions in U5MR inequality over a 10 year period. Contributing factors include overall economic growth and poverty reduction, improved insurance coverage, and a scaling-up and more equitable distribution of primary health-care infrastructure and intervention coverage. Understanding the factors that have led to Thailand's success could help inform countries struggling to meet the fourth MDG and reduce inequality. © 2007 Elsevier Ltd. All rights reserved.